Helping Families of Infants With Persistent Crying and Sleep Problems in a Day-Clinic - Singh, Binu S. K.; Danckaerts, Marina; Van den Bergh, Bea R. H. (Frontiers in Psychiatry, 2021)
Excessive crying and sleep problems affect up to 30% of infants and often coexist. Although usually benign and self-limiting, persistent crying and sleep problems exceeding 6 months of age need attention as they may impair the mental health of the infant and its family. The source and the impact of these persistent regulatory problems is often not restricted to the infant, but extends to the parents and the parent-infant relationship. Clinical practice needs interdisciplinary and multi-method interventions focusing beyond regulatory problems of the infant but also on parental self-regulation and parent’s co-regulatory responses toward the infant. Treating clinicians may encounter limitations of home-visits, outpatient and pediatric residential settings when working with families in distress. We describe an infant mental health day-clinic treatment, drawing attention to this viable future direction. It offers a therapeutic climate based on forming a triangle of co-regulation between clinician, parent and infant to first help the parent and the infant settle down. This stress reduction restores parent-infant connectedness and parental learning and reflecting capacity. Clinicians then use established therapeutic modalities to support parental self- and co-regulatory skills which is important for the development of self-regulation in the infant. Experience with this treatment program suggests that a day-clinic setting facilitates interdisciplinary and integrative multi-method intervention, infant and parental stress reduction and integration of parental self- and co-regulatory skills in daily family life, improving overall outcomes. This perspective warrants further investigation.